Catalase‐Encapsulated Nanoparticles via Surface Radical Polymerization for Periodontitis Therapy - Tongtong Yan; Xiang Li; Shiqun Sun; Yuchao Luo; Haotian Shi; Nan Yang; Xue Ren; Wenjing Tian; Zhihui Liu; Bin Xu (Macromolecular Materials and Engineering)
Abstract Periodontitis is a prevalent chronic inflammatory disease characterized by oxidative stress and excessive production of reactive oxygen species (ROS), leading to the destruction of periodontal tissues. Despite existing treatments, the management of periodontitis remains challenging due to inadequate control of inflammation and poor tissue regeneration. In this study, a novel therapeutic strategy is developed by encapsulating catalase (CAT) within polyacrylamide (PAAM)‐based nanoparticles (CAT NPs) through surface radical polymerization to enhance its stability and efficacy in the inflammatory environment of periodontal tissues. The PAAM polymer shell serves as a protective barrier to isolate CAT from interactions with proteolytic enzymes and inflammatory mediators in the periodontal microenvironment, thereby preventing structural denaturation and enhancing enzymatic stability. This approach targets the reduction of ROS levels and the modulation of the Nrf‐2/HO‐1 antioxidant pathway, key mediators in oxidative stress responses. In vitro and in vivo studies demonstrated that CAT NPs significantly alleviate oxidative stress, reduce pro‐inflammatory cytokines, and promote periodontal tissue regeneration. Compared to conventional treatments, CAT NPs exhibit superior therapeutic outcomes, offering a promising and long‐lasting solution for the treatment of periodontitis. This innovative strategy provides new avenues for the development of more effective periodontitis therapies.